2006
DOI: 10.1891/0047-2220.37.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Transition-Age Adults with ADHD: Gender and Predictors of Vocational Rehabilitation Outcomes

Abstract: Differences in rates of case closure, case service cost, hours worked per week, and weekly wage between White males and females with Attention Deficit/Hyperactivity Disorder were examined using the Rehabilitation Service Administration national data base of 2002. Females had statistically significantly higher case service costs than males. Using logistic regression, the customer demographic variable related to successful competitive employment for males was age. Case service variables related to successful com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Dutta et al (2008) also examined the effects of VR services on VR consumers with primary disabilities that were categorized as physical or mental and found that the likelihood of employment at closure for VR consumers with sensory impairments, physical impairments, and mental impairments, who received job placement services, increased by 1.66 times, 2.23 times, and 2.12 times, res pe ctively, compared with those who did not receive job placement services. Job placement assistance was also found to signi ficantly increase the likelihood of employment for male VR consumers with attention-deficit/ hyperactivity disorder (ADHD) by approximately 2 times (Schaller, Yang, & Trainor, 2006). Several studies on concerns and barriers to employment among unemployed individuals with HIV/AIDS have reported that unemployed individuals living with HIV/AIDS often experience difficulties in finding a job (Brooks & Klosinski, 1999;Hergenrather, Rhodes, & Clark, 2004;Hergenrather et al, 2005Hergenrather et al, , 2006Timmons & Fesko, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Dutta et al (2008) also examined the effects of VR services on VR consumers with primary disabilities that were categorized as physical or mental and found that the likelihood of employment at closure for VR consumers with sensory impairments, physical impairments, and mental impairments, who received job placement services, increased by 1.66 times, 2.23 times, and 2.12 times, res pe ctively, compared with those who did not receive job placement services. Job placement assistance was also found to signi ficantly increase the likelihood of employment for male VR consumers with attention-deficit/ hyperactivity disorder (ADHD) by approximately 2 times (Schaller, Yang, & Trainor, 2006). Several studies on concerns and barriers to employment among unemployed individuals with HIV/AIDS have reported that unemployed individuals living with HIV/AIDS often experience difficulties in finding a job (Brooks & Klosinski, 1999;Hergenrather, Rhodes, & Clark, 2004;Hergenrather et al, 2005Hergenrather et al, , 2006Timmons & Fesko, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Among students with disabilities at post-secondary institutions, students with LD and ADHD are the largest subgroup of this population (Gregg, 2009). These adult disability populations are also commonly served through vocational rehabilitation (Dowdy et al, 1992;Gregg, 2009;Schaller et al, 2006). Rehabilitation strategies for these populations include psychoeducation, behavioral training, psychotherapy, medication, social skills training, remediation methods, classroom management and support, parent training, support groups, lifestyle changes, and vocational and career guidance (Skinner, 2003;Vyas, 2021).…”
mentioning
confidence: 99%